Educational Approach: Application of SWOT Analysis for Assessing Entrepreneurial Goals in Senior Dental Students - Maria Antoniadou; Antonia Kanellopoulou (MDPI AG, 2024)
The SWOT (strengths, weaknesses, opportunities, and threats) analysis is a framework used to evaluate a company's competitive position and to develop strategic planning. In the competitive dental sector, it can aid dentists in identifying and analyzing internal strengths and weaknesses, as well as external opportunities and threats. This study focuses on senior dental students of the Department of Dentistry at the National and Kapodistrian University of Athens, Greece, aiming to scrutinize their use of SWOT analysis and assess its application as a tool for evaluating entrepreneurial goals and making career decisions in dental entrepreneurship. The research sample comprises 116 senior dental students (N1) in the final undergraduate year of their dental education, with data collection accomplished through the administration of an e-questionnaire during the obligatory course of "Organization and management of dental practices" in December 2023. The data extracted from the SWOT analysis encompass internal and external factors, gender distinctions, and outcomes derived from Stepwise Binary Logistic Regression concerning predictor markers. The results from the SWOT analysis of 114 valid questionnaires (N2), revealed that participants identified communication skills (50%) and organization skills (49.10%) as their primary strengths, followed by favorable personal traits contributing to goal success (36%). Weaknesses predominantly centered around emotional and personal traits like anxiety (41.20%) and other characteristics, alongside practical challenges such as lack of initial capital (24.60%). Main opportunities included collaboration with experienced dentists (33.30%) and access to training programs (27.20%), while economic instability in Greece (77.20%) and the saturated dentist profession (26.30%) were perceived as significant threats. Gender differences were notable, with female dentists more likely to report organization skills as a strength and anxiety as a weakness. Values such as industriousness, persistence, and ethics were commonly shared, with actions focusing on training programs (57.9%) and gaining experience with experienced dentists (29.8%). Cluster analysis identified two subgroups, with one emphasizing utilizing all available options (n = 49) and the other prioritizing on gaining professional skills and experience (n = 65). Logistic regression indicated that participants valuing industriousness were less likely to explore all available options, while those recognizing personal traits were more likely to do so. The study's outcomes highlight key predictor factors linked to a proactive orientation in career decision-making among senior dental students. These insights offer valuable implications for educational institutions and career counselors.